Inequality and Poverty in Galicia between 2007 and 2010. How is the Distribution of Crisis Effects? - Corbelle Cacabelos, , Fernando; Troitiño Cobas, , Angela (Revista Galega de Economía)
The aim of this work is to analyse the effects that the current economic crisis is producing on the Galician income distribution. We use three key variables: i) household disposable income, ii) household disposable income excluding the provision by unemployment, to measure the effect of such provision, iii) household disposable income including the imputed rent. We select inequality and poverty measures with good properties (Gini, Atkinson, Theil, FGT) and, using the Living Conditions Surveys (ECV) of the Galician Statistics Institute (IGE) as data base, we calculate inequality and poverty indexes and his variation between 2007 to 2010 year. The results show that the population with the lowest income diminishes his participation in the total income, what indicates us that the crisis is affecting more to the poorest. The inequality and poverty indexes increase in general, and with more intensity when excluding the provision by unemployment. The crisis is modifying the Galician poverty map, from the inner areas more aged (with pensions that work like antipoverty shield) to the Atlantic areas with younger population and more affected by the unemployment.